Effectiveness of leader-targeted stress management interventions: a systematic review and meta-analysis - Dannheim, Indra; Ludwig-Walz, Helena; Kirsch, Halina; Bujard, Martin; Buyken, Anette E.; Richardson, Katherine M.; Kroke, Anja (Scandinavian journal of work, environment & health, 2025)
Objective: Based on the well-documented role of supervisors` in fostering healthy workplaces and managing the impact of work-related stress, the aim of this study was to determine the effectiveness of leader-targeted stress management interventions (SMI) on their psychological stress, mindfulness, mental health, and work- and leadership-related outcomes. Methods: Eligible studies, including randomized controlled trials or controlled before–after studies, examining the effects of leader-targeted SMI on supervisors` psychological stress, mindfulness, mental health, and work- and leadership-related outcomes, were identified in four electronic databases and supplemented by manual search strategies. Screening for eligibility, data extraction, risk of bias assessment, and certainty of evidence grading, following PRISMA guidelines and Cochrane Handbook recommendations, were done in duplicate. Data were pooled in random effects models to synthesize g-scores. Sensitivity and moderator analyses were used to assess the robustness of the results and explore potential sources of heterogeneity. Results: The 25 studies (N=2466 participants) meeting the full inclusion criteria varied widely in population characteristics, intervention types, duration, delivery methods, and examined outcomes. The overall intervention effect was g=0.13 [95% confidence interval (CI) -0.24– -0.01] after excluding outliers. Significant intervention effects were found for mental health [g=-0.38 (95% CI -0.69– -0.08)] and, after excluding influential cases, work- [g=-0.32 (95% CI -0.63– -0.00)] and leadership-related outcomes [g=-0.23 (95% CI -0.44– -0.02)]. Conclusion: Our meta-analysis suggests that leader-targeted SMI can be an effective approach for promoting occupational health.
Online veröffentlicht: 18. März 2025
Gesehen am 13.08.2025